Studi Literatur: Manajemen Kualitas Total dalam Pengembangan Teknologi Pertahanan - Ayu Andinie; I Nengah Putra Apriyanto; Aries Sudiarso (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
This research examines the implementation of Total Quality Management (TQM) in the context of defence technology development through a comparative literature study. By analyzing 47 scientific publications from 2015-2024, this study identifies TQM practices applied by defence industries across various countries, analyzes their impact on organizational performance, and compares their implementation success. The analysis results show that TQM implementation has contributed significantly to improving development process efficiency, reducing production defects by up to 32%, and increasing defence system reliability by 27.5%. This research concludes that implementing TQM in the defence industry requires a specialized approach that considers technological complexity, strict security requirements, and the involvement of various stakeholders. Strategic recommendations are proposed to optimize TQM implementation in supporting national defence industry self-reliance.